Language documentation and revitalization in Latin American contexts - Pérez Báez, Gabriela; Rogers, Chris, 1977-; Rosés Labrada, Jorge Emilio (Trends in linguistics. Studies and monographs, 2016)
Up to now, the focus in the field of language documentation has been predominantly on North American and Australian languages. However, the greatest genetic diversity in languages is found in Latin America, home to over 100 distinct language families. This book gives the Latin American context the attention it requires by consolidating the work of field researchers experienced in the region into one volume for the first time.